Implementación de un sistema de control de velocidad para un prototipo tipo bicicleta para terapia en personas con pérdida de movilidad en los miembros inferiores. (2023)
Based on the data provided by the Dane until the year 2022, a percentage of 27.9% of the population in Colombia has problems in the lower extremities, causing a small part of this population to purchase rehabilitation equipment to replace the program activities in a place assisted by professionals. To mitigate this problem, an existing design of four-bar mechanisms is improved, with the adaptation of an electronic design that uses Arduino programming in order to control the gear motor for a specific time less than 10 minutes and this can be used in patients with loss of mobility. By means of an explanatory methodology, the proposed design is defined, developed and verified. On the other hand, a gear motor was used which has a voltage of 12 V with a consumption of 2 A, which has 45 RPM on this equipment. For the prototype it was characterized for being a mechanism designed with a load support of 28 Kg, being displaced by the gear motor, allowing a controlled pedaling according to the time programmed by the user. It was proved that the PID speed control allows from the simulation to eliminate the peaks that alter the operation of the motor rpm at its maximum point of 45 rpm and for its midpoint of 25 rpm. As a conclusion, the constant variables of the PID were calculated and verified by simulation and its programming was carried out by means of Arduino which allowed the control of the RPM of the motor from the times in minutes or seconds.